Maternal exposure to polystyrene nanoplastics during gestation and lactation caused fertility decline in female mouse offspring - Xiu Cheng; Yue Xue; Houpeng Wang; Zhangqiang Ma; Na Hu; Chenchen Zhang; Yu Gao; Ruihong Fan; Liaoliao Hu; Jia Li; Dalei Zhang; Jian Huang; et al. (Ecotoxicology and Environmental Safety)
The impact of micro/nano plastics (MPs/NPs) on human health is a significant area of research. Studies on the effects of maternal exposure to microplastics (MPs) on the fertility in offspring have been conducted, but the damage caused by nanoplastics (NPs) remains ambiguous. In this study, pregnant Kunming mice were exposed to 30 mg/kg/day PS-NPs from 0.5 gestation day (GD) to 21 days postpartum (dpp). Increased rates of miscarriage and premature delivery were observed, as well as reduced litter size, indicating potential permanent reproductive injury in mice of PS-NPs group. Maternal exposure to PS-NPs impaired fertility of the female offsprings. Decreased primordial and increased growing follicles were observed in the ovaries of offspring at 1 dpp and 7 dpp in PS-NPs group, indicating premature activation of primordial follicles. This premature activation is likely due to the PS-NPs'induction of the AKT-FOXO3a signaling pathway by downregulating AMPK phosphorylation level and enhancing mTOR activity. Furthermore, a significant reduction in transzonal projections (TZPs) was noted in the ovaries of adult offspring mice in PS-NPs group. RNA sequencing of the ovaries from adult offspring female mice revealed that the TZPs related genes may be linked to CAMKIIβ, with a corresponding downregulation in expression levels. Overall, maternal exposure to PS-NPs induced profound and enduring effects on the reproductive functions of female offspring, raising critical alarms regarding the multigenerational reproductive toxicity risks associated with nanoplastic exposure in mammals.